Pengaruh Pembiasaan Membaca Al-Qur’an Setiap Pergantian Jam Pelajaran Terhadap Kesiapan Mental Mahasiswa Genta Pare Kediri - Erviana Sofyan; Rofiatul Hosna (Al-Misbah (Jurnal Islamic Studies), 2019)
This study discusses the effect of quran reading habits on mental readiness, this is motivated by the many students who complain about the lessons learned, it is necessary to have mental readiness when receiving lessons, one of which is to get used to reading the Qur'an. This habituation aims to improve the intelligence of the brain and memory of a person, and can nourish various kinds of physical and psychological illnesses. The purpose of this study is (1) To find out and analyze the habit of reading the Qur'an every turn of the lesson, (2) To find out and analyze mental readiness, (3) To find out and analyze the influence of the habit of reading the Qur'an every turn lesson hours for students' mental readiness in the Golden English Training Area (GENTA) Pare Kediri. In this study, the study design used a quantitative approach with Expost Facto design and used a type of field research. The population in this study were all D1 GENTA Pare students. Sampling in this study used Simple Random Sampling. So that every sample withdrawal using this method provides the same opportunity for each member of the population to be a research sample. In this study, data collection uses a questionnaire that serves to measure the level of mental readiness of students who are influenced by the habit of reading the Qur'an.